Falsas memórias em tarefas de curto prazo: efeitos do interva- lo de retenção e da emocionalidade - Sene, Arthur Siqueira de (2011)
False Memories (FM\'s) are memory errors that occur when people remember situations that did not happen, events not witnessed, or when the memory of the facts are distorted. The aim of this study was to evaluate the occurrence of false memories in a short-term task using the Deese-Roediger-McDermott (DRM) procedure. We planned out two experiments: the first experiment is an adaptation based on the Coane, McBride, Raulerson and Jordan (2007) experiments and it was performed by 12 participants. Sets of memorized words (CPM) composed of 3, 5 or 7 items and type of test (target, critical distractor and distractor not related) were manipulated within subjects. The main dependent variable was the reaction time (RT). The variable type of test was statistically significant, while the interaction between CPM and CPM x type of test were not statistically significant. The second experiment was performed by two groups of 12 participants. In the group 1 the retention interval was 750ms, while in the group 2 the retention interval was 1500ms. We also manipulated the CPM, the type of test and the emotionality / valence (positive, neutral and negative) of the words. The retention interval was not statistically significant, while the type of test and the CPM were statistically significant. The variable emotionality / valence (positive, neutral and negative) was not statistically significant. In general, the data replicate the Coane et al\'s work, except in the experiment 1, in which the CPM was not significant. The presence of FMs in the two experiments shows the generality and robustness of this phenomenon, widely found in the literature. The results were discussed in terms of the main theories about the phenomenon of false memories.